Effect of Hydroxytyrosol Derivatives of Donepezil on the Activity of Enzymes Involved in Neurodegenerative Diseases and Oxidative Damage - Antonio D’Errico; Rosarita Nasso; Rosario Rullo; Jessica Maiuolo; Paola Costanzo; Sonia Bonacci; Manuela Oliverio; Emmanuele De Vendittis; Mariorosario Masullo; Rosaria Arcone (Molecules, 2024)
Monoamine oxidase and xanthine oxidase inhibitors represent useful multi-target drugs for the prevention, attenuation, and treatment of oxidative damage and neurodegenerative disorders. Chimeric molecules, constituted by naturally derived compounds linked to drugs, represent lead compounds to be explored for the discovery of new synthetic drugs acting as enzyme inhibitors. We have previously reported that seven hydroxytyrosol-donepezil hybrid compounds play a protective role in an in vitro neuronal cell model of Alzheimer’s disease. In this work, we analyzed the effects exerted by the hybrid compounds on the activity of monoamine oxidase A (MAO-A) and B (MAO-B), as well as on xanthine oxidase (XO), enzymes involved in both neurodegenerative disorders and oxidative stress. The results pointed to the identification, among the compounds tested, of selective inhibitors between the two classes of enzymes. While the 4-hydroxy-3-methoxyphenethyl 1-benzylpiperidine-4-carboxylate- (HT3) and the 4-hydroxyphenethyl 1-benzylpiperidine-4-carboxylate- donepezil derivatives (HT4) represented the best inhibitors of MAO-A, with a scarce effect on MAO-B, they were almost ineffective on XO. On the other hand, the 4,5-dihydroxy-2-nitrophenethyl 1-benzylpiperidine-4-carboxylate donepezil derivative (HT2), the least efficient MAO inhibitor, acted like the best XO inhibitor. Therefore, the differential enzymatic targets identified among the hybrid compounds synthesized enhance the possible applications of these polyphenol-donepezil hybrids in neurodegenerative disorders and oxidative stress.